The Effect of Latex on The Characteristics of Asphalt Concrete Wearing Course - Sartika Nisumanti; Ghina Amalia; SA Putri (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The Laston has a high degree of flexibility, located above the surface layer, this layer is susceptible to damage due to high temperatures, more. Asphalt as a pavement if spread will experience hardening, so that additional materials are added to make it flexible. The AC-WC mixture uses 60/70 penetration asphalt with the addition of latex. The purpose of knowing the characteristics of the marshall AC-WC mixture at the optimum asphalt content. The addition of latex 3%, 5%, 9% of the total volume of asphalt. The process is through heating asphalt and then adding latex, the proportion of aggregate is based on the ideal mixture gradation. Samples were made on hot mixture by Marshall test method. The results showed that the selected AC-WC mixture with a latex variation of 3% of the total, all asphalt properties were met. Stability 3201.1, Flow 2.4, MQ 1679,339kg, VIM 5% VMA 17.799%, VFA 74.426%.